2016
DOI: 10.1186/s12890-016-0291-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of comparative studies of tiotropium Respimat® and tiotropium HandiHaler® in patients with chronic obstructive pulmonary disease: does inhaler choice matter?

Abstract: BackgroundIn many countries worldwide, the long-acting anticholinergic drug tiotropium is available as a dry powder formulation delivered by means of the HandiHaler® inhalation device and as an aqueous solution delivered via the Respimat® Soft Mist™ Inhaler. Tiotropium HandiHaler® is a single-dose, dry powder, breath-actuated inhaler that provides delivered doses and lung deposition of tiotropium that are, over a wide range, not influenced by the severity of chronic obstructive pulmonary disease (COPD). Tiotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…The timing of this study in the summer of 2019 coincided with a period in which the HandiHalerÒ was predominantly used for delivery of TIO, and as such led to the use of the HandiHalerÒ as a comparator device in the current analysis. However, clinical outcomes were similar with TIO delivered using the HandiHalerÒ and the RespimatÒ (5 lg dose), suggesting that patient-dependent factors are the key consideration for selection between the two devices [30]. While there are no direct comparisons of drug delivery by SMIs, DPIs, and nebulizers, drug aerosol properties and delivery tend to be improved with nebulizers and SMIs compared with DPIs [41].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The timing of this study in the summer of 2019 coincided with a period in which the HandiHalerÒ was predominantly used for delivery of TIO, and as such led to the use of the HandiHalerÒ as a comparator device in the current analysis. However, clinical outcomes were similar with TIO delivered using the HandiHalerÒ and the RespimatÒ (5 lg dose), suggesting that patient-dependent factors are the key consideration for selection between the two devices [30]. While there are no direct comparisons of drug delivery by SMIs, DPIs, and nebulizers, drug aerosol properties and delivery tend to be improved with nebulizers and SMIs compared with DPIs [41].…”
Section: Discussionmentioning
confidence: 87%
“…Prior comparisons of inhaler devices have been performed and showed differences between inhalers [27][28][29][30][31], but comparisons of the aerosol performance and drug deposition with nebulizers are limited. In addition, the previous analysis of the aerosol performance and drug deposition of GLY delivered using the eFlowÒ CS nebulizer assessed characteristics at constant flow or a single tidal volume, consistent with normal patients [32].…”
Section: Introductionmentioning
confidence: 99%
“…Since device satisfaction has been associated with better outcomes, 13,14,40,42,[65][66][67] it seems prudent for clinicians to consider patient preferences during the device selection process. Indeed, GOLD treatment strategies recommend that device selection be based not only on medication availability, costs, and the prescribing physician's preferences, but also on the patient's device preferences and the ability to use the inhalation device.…”
Section: Discussionmentioning
confidence: 99%
“…Device use errors were based on the patients' ability to correctly complete the following 14 inhalation steps: 10 (1) checking the cartridge or capsule, (2) holding the inhaler in the upright position, (3) turning the base in the direction of the arrows until it clicks, (4) opening the cap, (5) not activating the inhaler inadvertently, (6) exhaling completely and away from the inhaler, (7) closing lips around the mouthpiece, (8) holding the inhaler in a horizontal position so that it is pointing to the back of throat, (9) pressing the doserelease button while taking a slow and deep inhalation, (10) continuing to inhale slowly and deeply through the mouth, (11) holding breath up to 10 seconds, (12) removing the inhaler from the mouth and breathing out, (13) repeating steps for the second puff, and (14) closing the cap. Dose preparation (priming) steps for first time device use were excluded from the analyses since only two studies 39,40 reported these types of errors.…”
Section: Respimat Smi Device Use Stepsmentioning
confidence: 99%
“…In qualitative research, patients indicated that non-consented inhaler switches resulted in a worse relationship with their doctor, less confidence in their medication and worse disease control perception [43]. Changing the device, but continuing the same medication at equivalent dosing, does not reduce drug efficacy [44].…”
Section: Patient Preferencesmentioning
confidence: 99%